2020
DOI: 10.15171/ijhpm.2020.10
|View full text |Cite
|
Sign up to set email alerts
|

Global Problem of Hospital Detention Practices

Abstract: Although an official definition by the World Health Organization (WHO) or any other authority is currently lacking, hospital detention practices (HDP) can be described as: "refusing release of either living patients after medical discharge is clinically indicated or refusing release of bodies of deceased patients if families are unable to pay their hospital bills. " Reports of HDP are very scarce and lack consistent terminology. Consequently, the problem's scale is unknown. This study aimed to find evidence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Hospitals must not detain patients for their inability to pay [21]. It reported that patients are detained for non-paying the cost of treatment in Bangladesh [37,38] and other countries [39] thus violates patients right to healthcare. The human rights framework in patient care calls for policy and legislation that ensures protection of the legal and human rights of both patients and healthcare providers [21].…”
Section: Literature On Right To Healthcarementioning
confidence: 99%
“…Hospitals must not detain patients for their inability to pay [21]. It reported that patients are detained for non-paying the cost of treatment in Bangladesh [37,38] and other countries [39] thus violates patients right to healthcare. The human rights framework in patient care calls for policy and legislation that ensures protection of the legal and human rights of both patients and healthcare providers [21].…”
Section: Literature On Right To Healthcarementioning
confidence: 99%
“…Though found in at least 46 nations, its broader prevalence is unknown. The few surveys of the practice that have been done rely almost exclusively on accounts of detention that appear in local news media for a select set of Western languages (Handayani et al., 2020; Mostert et al., 2015). Nonetheless, scholars concur that most detainees are obstetric patients, usually following cesarean sections (Cowgill & Ntambue, 2019, 12; Devakumar & Yates, 2016).…”
Section: Background On Hospital Detentionmentioning
confidence: 99%